A review of air travel behavior and climate change. (18th August 2022) - Gössling, Stefan; Dolnicar, Sara
Abstract: Air transport challenges the world's net‐zero carbon ambitions. The sector has consistently grown and causes warming as a result of both CO2 and other, short‐lived emissions. Two principal solutions have been proposed to reduce the contribution of aviation to climate change: innovations of technology and the development of interventions to trigger behavioral change. Technological innovations include new propulsion technologies and the use of sustainable aviation fuels. Behavioral change includes flight avoidance, substitution with other means of transport, the choice of efficient flight options, and carbon offsetting. This article focuses on behavior; it offers an overview of factors that lead to consumers traveling by air and discusses demand distribution complexities. The importance of price for air travel decisions is assessed, and evidence of travel "wants" are contrasted with "needs, " the latter investigated in light of the COVID‐19 pandemic. The review of relevant scholarly work culminates in an action list enabling air travelers, policy makers, the aviation industry, researchers and society to meaningfully advance low‐carbon air transport trajectories. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior Abstract : Air travel mitigation responses.